Penerapan Problem Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik Mata Pelajaran Pendidikan Pancasila Kelas V SDN 02 Podorejo - Manik Mustiko Bayu; Sintiya Pujiana; Susilo Tri Widodo; Rina Nuraeni; Budi Santoso (Journal on Education, 2025)
This research was conducted to determine the effect of problem-based learning on improving student learning outcomes in the Pancasila Education subject class v SD Negeri 2 Podorejo, with a total of 27 students consisting of 10 male students and 17 female students. This research uses a descriptive classroom action research method. Data collection techniques past interviews with the head of the class teacher and the researcher also carried out phase I and II learning cycles. The results of this research show that some students are very enthusiastic during learning activities and participate actively. Students with high intelligence easily understand the material and get high grades, while students with low levels of ability tend to have difficulty and get low grades. The researcher encountered two obstacles; first, the researcher still needed to recognize and understand the characteristics of each student and the time limitations in carrying out the learning cycle.